2015
DOI: 10.1149/2.0151509jss
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Copper Gettering Mechanism of Oxide Precipitates in Silicon

Abstract: One of the reasons why the principal gettering mechanism of copper at oxide precipitates is not yet clarified is that it was not possible to identify the presence and measure the copper concentration in the vicinity of oxide precipitates. To overcome the problem we used a 14.5 nm thick thermal oxide layer as a model system for an oxide precipitate to localize the place where the copper is collected. We also analyzed a plate-like oxide precipitate by EDX and EELS and compared the results with the analysis carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
2
30
0
3
Order By: Relevance
“…By this technique, a lateral resolution of better than 1.5 nm has been already demonstrated. 40 The silicon plasmon ratio mappings obtained by this technique display the silicon nanostructure in the nc-SiO x :H layers as shown in The HRTEM examinations of the nanostructure of ncSiO x :H layers validate the presence of silicon nanocrystals. An HRTEM image of a cross-sectioned nc-SiO x :H type B layer deposited at 1067 Pa is presented in Fig.…”
Section: Nanostructurementioning
confidence: 78%
“…By this technique, a lateral resolution of better than 1.5 nm has been already demonstrated. 40 The silicon plasmon ratio mappings obtained by this technique display the silicon nanostructure in the nc-SiO x :H layers as shown in The HRTEM examinations of the nanostructure of ncSiO x :H layers validate the presence of silicon nanocrystals. An HRTEM image of a cross-sectioned nc-SiO x :H type B layer deposited at 1067 Pa is presented in Fig.…”
Section: Nanostructurementioning
confidence: 78%
“…1 In both cases, between SiO 2 existing in the center of the precipitate and in the oxide layer and Si of the matrix and the substrate a suboxide region of 2-3 nm was found. These results were obtained by electron energy loss spectrometry (EELS) carried out by scanning transmission electron microscopy (STEM).…”
mentioning
confidence: 90%
“…[2][3][4] It was also demonstrated that metallic impurities can be effectively trapped at oxygen precipitates in the process of gettering. [5][6][7][8][9] All these features of the oxygen precipitates require the control of precipitation in the production process of silicon devices. However, this cannot be optimally executed if the features of oxygen precipitates like their composition are not fully known.…”
mentioning
confidence: 99%